Decomposing Social Sustainability: Signaling Theory Insights into Supplier Selection Decisions. Issue 4 (15th December 2020) - Thomas, Rodney; Darby, Jessica L.; Dobrzykowski, David; van Hoek, Remko
Abstract : Social sustainability has emerged as a key determinant in supplier selection. However, firms may approach social sustainability in varying ways such as investments in employee welfare or philanthropy. Little is known about how supply chain managers consider these individual dimensions when making sourcing decisions. Therefore, this research decomposes social sustainability into dimensions of employee welfare and philanthropy to determine their effects on supplier selection. Vignette‐based experiments in a transportation context test a priori hypotheses derived from signaling theory, and post hoc qualitative insights reveal deeper understanding. Results show buyers have significant preferences to select, trust, and collaborate with suppliers who have desirable levels of employee welfare, philanthropy, and pricing. However, these findings are tempered by differential effect sizes and suggest that the practical significance of hypothesized relationships vary. These findings help refine our understanding of social sustainability conceptualizations and evolving supplier selection criteria, as well as offer timely insights for suppliers, buyers, and policymakers amidst surging demand for social sustainability.